PERAN PERATURAN PERUNDANG-UNDANGAN DALAM MENJAMIN PERLINDUNGAN HAK ASASI MANUSIA DI INDONESIA - Adriel Rivaldo Neno; Pankrasius Yosepsina Lamen; Moraldi Moses Taniu; Vicki Yunus Takene; Wisley Ejandro Koebanu; Fadil Mas’ud (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Human Rights (HAM) are fundamental rights inherent in every human being from birth and must be respected, upheld, and protected by the state. In a constitutional state like Indonesia, human rights protection is realized through various laws and regulations that govern the rights and obligations of citizens. This study aims to analyze the role of laws and regulations in guaranteeing human rights protection in Indonesia and the obstacles to their implementation. The research method used is normative legal research with a regulatory approach and a contextual approach. The results show that Indonesia has a fairly strong legal basis for human rights protection, starting from the 1945 Constitution, Law Number 39 of 1999 concerning Human Rights, and various other regulations. However, the implementation of human rights protection still faces various challenges such as weak law enforcement, overlapping regulations, and the persistence of human rights violations in various sectors of life. Therefore, it is necessary to strengthen the legal system, increase public awareness, and government consistency in upholding human rights principles.